2021
DOI: 10.1038/s41598-021-81972-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of Behçet disease with psoriasis and psoriatic arthritis

Abstract: Behçet disease (BD) is a debilitating multi-systemic vasculitis with a litany of muco-cutaneous manifestations and potentially lethal complications. Meanwhile, psoriasis (PSO) is a cutaneous and systemic inflammatory disorder marked by hyperplastic epidermis and silvery scales, which may be accompanied by a distinct form of arthropathy called psoriatic arthritis (PsA). While the clinical pictures of these two are quite different, they feature some important similarities, most of which may stem from the autoinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…An association was also confirmed between psoriasis and hearing loss (217), Behcȩt's disease (218), scabies infection (219), and pediatric infection (220).…”
Section: Rare Comorbiditiesmentioning
confidence: 92%
“…An association was also confirmed between psoriasis and hearing loss (217), Behcȩt's disease (218), scabies infection (219), and pediatric infection (220).…”
Section: Rare Comorbiditiesmentioning
confidence: 92%
“…[39][40][41][42][43][44][45][46][47][48][49][50] It is also well-known that, some of these above-mentioned inflammatory diseases (i.e., inflammatory bowel diseases, psoriasis, and systemic lupus erythematosus) have an intersection with BS. [51][52][53] Similar to CLEC12A , IFI27 is also among the top 10 most differentially ex-pressed genes of the class comparisons (second in M vs. C with an FC: 3.49, second in Ovs. C with an FC: 2.14, and third in V vs. C with an FC: 4.34) (Table 6).…”
Section: Discussionmentioning
confidence: 81%
“… 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 It is also well‐known that, some of these above‐mentioned inflammatory diseases (i.e., inflammatory bowel diseases, psoriasis, and systemic lupus erythematosus) have an intersection with BS. 51 , 52 , 53 Regarding interferons in BS, Belguendouz et al reported an increased in vivo and in vitro production of interferon gamma in active ocular BS patients compared to inactive patients and healthy controls. 54 Additionally in the same study, interferon gamma was shown to induce nitric oxide production in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The literature harbors many inflammatory/immunological conditions including inflammatory bowel diseases, psoriasis, systemic lupus erythematosus, Sjögren's syndrome, antiphospholipid syndrome, acute graft‐versus‐host disease, immune thrombocytopenic purpura, Aicardi−Goutieres syndrome, Kikuchi−Fujimoto, and hand, foot, and mouth diseases, in which significant increases in IFI27 expression have been reported 39–50 . It is also well‐known that, some of these above‐mentioned inflammatory diseases (i.e., inflammatory bowel diseases, psoriasis, and systemic lupus erythematosus) have an intersection with BS 51–53 . Regarding interferons in BS, Belguendouz et al reported an increased in vivo and in vitro production of interferon gamma in active ocular BS patients compared to inactive patients and healthy controls 54 .…”
Section: Discussionmentioning
confidence: 99%